Towards developing the skill of transcommunicating among tertiary education students: the role of study abroad programmes - Bielak, Marlena Iwona (Scripta Neophilologica Posnaniensia, 2020)
The objective of the paper is to highlight the need of adjusting the skills of tertiary education graduates to the requirements of the present global world, which entails the idea that higher education should be aimed at developing abilities that will facilitate communicating within and across a variety of communities, ethnicities and cultures. In the paper it is postulated that tertiary education graduates should be equipped, inter alia, with the skill of transcomunicating based on the idea of equality of cultures and languages. Due attention is paid to the role of study abroad programmes in the aforementioned process. Accordingly, the research part of the paper delves into the influence of the Erasmus+ mobility on the development of transcommunication among tertiary education students and rests on the analysis of the material gathered during interviews with learners who participated in the international student mobility conducted within The Erasmus+ Framework. The research results point to the key role of experiential learning held in territorial contexts in the process of developing the skill of transcommunicating among the research participants.